A Method of Effective Quarry Water Purifying Using Artificial Filtering Arrays; IOP Conference Series: Earth and Environmental Science; Vol. 50 : Ecology and safety in the technosphere: current problems and solutions - Tyulenev M. A. Maksim Anatolievich; Garina E.; Khoreshok A. A. Aleksey Alekseevich; Litvin O.; Litvin Y.; Maliukhina E. (2017, 2017)
Title screen